EVALUASI KEPUASAN PASIEN TERHADAP APOTEK X DAN Y DI KOTA PONTIANAK - Yulia Wardati; Soni Spinnori; Ida Erna Widiyawati (Prodi Farmasi - Universitas Al Ghifari, 2023)
The location of the X and Y Pharmacies are close together on one road in the Pontianak Kota sub-district, the service looks the same, but the number of consumers who come is more dominant at the X Pharmacy. To be able to measure the quality of service, it is necessary to evaluate customer satisfaction. This study aims to determine patient satisfaction, assess the relationship between patient characteristics and determine the strength of the relationship characteristics and 5 dimensions to the services of Pharmacy X and Pharmacy Y. The survey was conducted using a cross sectional approach using a validated questionnaire instrument. The level of customer satisfaction was measured using the SERVQUAL (Service Quality) model for 5 dimensions of service quality, namely reliability, responsiveness, assurance, empathy, and tangible. Respondents in this study were 106 respondents to pharmacy X, while 102 respondents to pharmacy Y. using the method Based on 5 dimensions of service quality the overall average value of 5 dimensions at pharmacy X is 87.5%, while the overall average value of 5 dimensions at pharmacy Y is 56.5%. Based on the che-square test analysis, the value of the relationship between patient characteristics and pharmaceutical services at pharmacies X and Y was obtained, namely at pharmacy X there was a relationship between work (p-value = 0.016) and education (p-value = 0.047) but only work factor (p-value = 0.014) which had a relationship to patient assessment at pharmacy Y. 48, at the pharmacy Y 0.682. In conclusion, in general the patient satisfaction of the studied Pharmacy X was